Impediments to the advancement of human rights by the ZHRC in Zimbabwe - Chilunjika, Alouis; Tapfumaneyi, Nicol Tinashe; Zimano, Felistas R. (International Journal of Law and Public Policy, 2022)
Zimbabwe as a member of the United Nations (UN) ratified a number of human rights treaties and the establishment of the much awaited Zimbabwe Human Rights Commission (ZHRC) which was long overdue was a generally welcome development in the human rights arena. The ZHRC is a National Human Rights Institution (NHRI) established by the Constitution of Zimbabwe (No.20) Act 2013. The Constitution mandates ZHRC to promote, protect and enforce human rights and fundamental freedoms enshrined under the Bill of Rights. The operational legal framework of the ZHRC is provided for in the Zimbabwe Human Rights Commission Act [Chapter 10:30]. In collecting data questionnaires, interviews and documentary review were used. Against this backdrop, the paper mainly seeks to explore and analyse the challenges faced by the Zimbabwe Human Rights Commission (ZHRC) in executing its mandate. Methodologically, the study relied extensively on available literature and reports. The study revealed that the ZHRC has been impeded by resource constraints, absence of legally binding laws, hostile political environment and lack of state compliance experiencing impediments which have affected its operation. The therefore study made some recommendations to help fortify and reinvigorate the ZHRC.